Concomitant BCR-ABL and JAK2 V617F in a patient with myeloproliferative neoplasm: a case report - A, Alia Suzana; I, Azlin; A, Hafiza; Nor Rafeah Tumian,; Y, Siti Mariam; J, Norunaluwar; S, Salwati; RZ, Azma (Penerbit Universiti Kebangsaan Malaysia, 2023)
Myeloproliferative neoplasm (MPN) is a clonal proliferation of the haematopoietic stem cells leading to activated tyrosine kinase signaling activity. Myeloproliferative neoplasm is classified into BCR-ABL positive chronic myeloid leukemia (CML) and BCR-ABL negative MPN which harbors JAK2 V617F mutation in most cases. The genetic combination of BCR-ABL and JAK2 V617F mutation is rare with estimated frequency of 0.4% based on recent study. Herein, we reported a case of a man diagnosed with CML detected by fluorescence in-situ hybdridisation (FISH) showing atypical BCR-ABL fusion pattern in 29% nucleated cells (cut-off levels ≥5% for positive signals) in the presence of JAK2 V617F mutation. However, the BCR-ABL transcript was not detected by the conventional reverse transcriptase-polymerase chain reaction (RT-PCR) method which was specific for major fragments. Interestingly, complete hematological remission was not achieved despite initiation of tyrosine kinase inhibitor (Imatinib). In conclusion, it is imperative to scrutinise CML cases for concomitant JAK2 V617F mutation especially patients with atypical clinical or laboratory findings. Therefore, close monitoring with clinical and ancillary technique especially FISH and molecular methods such as DNA sequencing were crucial to help achieve complete hematological, cytogenetic and deep molecular response alongside targeted therapy.